Incidence of food and aero allergies among patients visiting Allergy center National Institute of Health (NIH), Islamabad - Sadaf Munir; Hammad Ahmad; Tayyib Ayub Alvi; Adnan Yousaf; Shahzad Akhter Kazi; Manzoor, Tayyeba (Journal of the Pakistan Medical Association, 2022)
Objective: To identify the most common allergy type among patients visiting an urban allergy centre. Methods: The descriptive cross-sectional study was conducted at the Allergy Centre of the National Institute of Health, Islamabad, Pakistan, from December 2019 to June 2020, and comprised subjects of either gender aged 20-50 years. Skin prick test was used to determine the skin reactivity for 11 common allergen extracts. Patients with a wheal diameter >3mm were considered positive. Data was analysed using SPSS 22. Results: Of the 100 patients, 55(55%) were males and 45(45%) were females. The overall mean age was 34.03±8.16 years. Majority of the respondents 93(93%) were sensitive to aeroallergen, 7(7%) to food allergens, and 2(2%) exhibited sensitivity against both types of allergens. Poly-sensitisation was found among 86(86%) respondents. Conclusion: Aeroallergens were found to be the main triggering factor for allergies compared to the food allergens. Continue...